THE PARTICIPANT MANAGEMENT OF DIRECTOR IS RELATED TO SCHOOL’S EFFECTIVENESS OF THE ISLAMIC PRIVATE SCHOOL IN NAKHON SI THAMMARAT - Phanprae, Sanma; Raksatham, Sompong; Chatakan , Werayut (Journal of MCU Nakhondhat, 2024)
This research aims to 1) to study the level of participatory management of school administrators Islamic private schools in Nakhon Si Thammarat. 2) to study the level of effectiveness of educational institutions of Islamic private schools in Nakhon Si Thammarat. 3) to study the relationship between administrators' participatory management and school effectiveness of Islamic private schools in Nakhon Si Thammarat. and 4) to study the participatory management development approach of administrators that relates to the effectiveness of educational institutes Islamic private schools in Nakhon Si Thammarat. The sample group consisted of 194 teachers. The research instrument was a questionnaire. Statistics used in data analysis included mean, standard deviation. and finding the Pearson correlation coefficient. The research results found that 1) Level of participatory management and each aspect was at a high level. 2) The level of effectiveness of the educational institution overall and in each aspect is at a high level. 3) The participatory management of educational institution administrators has a positive relationship with the educational institution's effectiveness at a high level. and 4) The results of the study of the participatory management development approach of the administrators that contribute to the effectiveness of educational institutes of Islamic private schools in Nakhon Si Thammarat Province found that school administrators must be allow personnel to participate in setting goals participatory management. They are must have the intention to create quality of students for society. In addition, you must decide on selecting effective personnel to match the job. The administrators must be trust and confidence them for helping and supporting various activities. There are participation in making decision or the management. The important process of management that creating love between executives and personnel.